Factors influencing inclination towards bribery among lower rank officers in the Malaysian immigration department - Lokman, Asmidar (2019)
The purpose of this study is to determine the best predictor in the inclination towards bribery among lower rank officers in the Malaysian Immigration Department (JIM). The factors, namely ethical orientation, significant others, individual values, gender, age and duration of service are theorised as factors directly influencing the inclination towards bribery. The four objectives are; first, to identify the level of ethical orientation, significant others and individual values on inclination towards bribery. The second objective is to examine the relationship between ethical orientation, significant others, individual values and inclination towards bribery. The third objective is to examine influence of socio-demographic patterns on inclination towards bribery. The fourth objective is to determine the most significant predictor of inclination towards bribery. The Bureaucratic theory was supported by the Unified Normative Ethics (UNE) theory to explain the behaviour is conducted based on the ‘what ought to be’ maxim reflecting the normative nature of public service.